Masterpieces of French literature - Severson, Marilyn S. (Greenwood introduces literary masterpieces, 2004)
"Provides a critical introduction to landmark novels in nineteenth- and twentieth-century French literature. Includes works that cover a time period of over 100 years and reflect both the development of the French novel during the era as well as themes, characters, and plots that appeal to readers in the twenty-first century."--GVRL description.